Ethnic and Sociocultural Differences in Ovarian Reserve: Age-Specific Anti-Müllerian Hormone Values and Antral Follicle Count for Women of the Arabian Peninsula - Melado, Laura; Vitorino, Raquel; Coughlan, Carol; Bixio, Leyla Depret; Arnanz, Ana; Elkhatib, Ibrahim; De Munck, Neelke; Fatemi, Human M.; Lawrenz, Barbara (Frontiers in Endocrinology, 2021)
Background: Anti-Müllerian hormone (AMH) and antral follicle count (AFC) age-specific reference values form the basis of infertility treatments, yet they were based upon studies performed primarily on Caucasian populations. However, they may vary across different age-matched ethnic populations. This study aimed to describe age-specific serum AMH and AFC for women native to the Arabian Peninsula. Methods: A retrospective large-scale study was performed including 2,495 women, aged 19 to 50 years, native to the Arabian Peninsula. AMH and AFC were measured as part of their fertility assessment at tertiary-care fertility centres. Age-specific values and nomograms were calculated. Results: 2,495 women were evaluated. Mean, standard deviation and median values were calculated for AMH and AFC by 1-year and 5-years intervals. Median age was 34.81 years, median AMH was 1.76ng/ml and median AFC was 11. From the total group, 40.60% presented with AMH levels below 1.3ng/mL. For women <45 years old, the decrease in AFC was between -0.6/-0.8 per year. Up to 36 years old, the decrease of AMH was 0.1ng/ml. However, from 36 to 40 years old, an accelerated decline of 0.23ng/ml yearly was noted. In keeping with local customs, 71.23% of women wore the hijab and 25.76% the niqab. AMH and AFC were significantly lower for niqab group compared with hijab group (p=0.02 and p=0.04, respectively). Conclusion: This is to-date the largest data set on age-specific AMH and AFC values in women from the Arabian Peninsula aiming to increase clinical awareness of the ovarian reserve in this population.